Inovação e ciclo de vida organizacional: o caso do setor de produção de cachaça da Paraíba - Santos, Jaysa Eliúde Aguia dos (2017)
This dissertation aims to analyze the behavior of innovations undertaken by cachaça producer organizations from the state of Paraíba and its precedents (drivers and enablers) throughout the Organizational Life Cycle. To reach this objective the methodological procedures were executed in two phases. The first was exploratory, in an attempt to characterize the cachaça producer organizations from Paraíba as to the stage of the Organizational Life Cycle, under a quantitative perspective, in which a survey was conducted using questionnaires with 23 cachaça distilleries from the state of Paraíba. In this phase the data were analyzed through the use of the Average Ranking technique and supported by the basic descriptive statistics. The second phase using a qualitative approach made use of the multiple case study research strategy in two cachaça distilleries selected from the results of the first phase of the study. In this new phase, the data were collected through semi-structured interviews, document analysis and systematic direct observation and treated through the technique of content analysis. The Phase I results showed that the cachaça distilleries in Paraíba are in different phases of the Organizational Life Cycle: seven in birth, eight in growth, three in maturity, three in the renewal phase, and two in the process of decline. Of these cachaça distilleries, two that (denominated cachaça distilleries A and B) are in the phase of renovation were selected from previously established criteria. The second phase results showed that both A and B cachaça distilleries developed product innovations with radical intensity, of process with radical and incremental intensity, of the organizational type with radical and incremental intensity and of marketing, with a radical and incremental character in the cachaça distilleries A, and with a radical degree in cachaça distilleries B, along its trajectories. The main innovation drivers evidenced were the market leadership and opportunity and the main factors that enabled the development of innovations in the cachaça distilleries were human resources and financial resources. It is concluded that the innovation way does not depend specifically on the configuration at a certain stage of the organizational life cycle, in other words, the direction to innovation must consider the characteristics of organizations in terms of strategy, structure, situation and style of decision making, beyond the resources possessed and the trajectory covered by the organization.